Lethal and sub-lethal effects of cyproconazole on freshwater organisms: a case study with Chironomus riparius and Dugesia tigrina - Saraiva, Althiéris S; Sarmento, Renato A; Golovko, Oksana; Randak, Tomas; Pestana, João L T; Soares, Amadeu M V M (Environmental science and pollution research international, 2018)
The fungicide cyproconazole (CPZ) inhibits the biosynthesis of ergosterol, an essential sterol component in fungal cell membrane and can also affect non-target organisms by its inhibitory effects on P450 monooxygenases. The predicted environmental concentration of CPZ is up to 49.05 μg/L and 145.89 μg/kg in surface waters and sediments, respectively, and information about CPZ toxicity towards non-target aquatic organisms is still limited. This study aimed to address the lack of ecotoxicological data for CPZ, and thus, an evaluation of the lethal and sub-lethal effects of CPZ was performed using two freshwater invertebrates (the midge Chironomus riparius and the planarian Dugesia tigrina). The estimated CPZ 48 h LC50 (95% CI) was 17.46 mg/L for C. riparius and 47.38 mg/L for D. tigrina. The emergence time (EmT50) of C. riparius was delayed by CPZ exposure from 0.76 mg/L. On the other hand, planarians showed higher tolerance to CPZ exposure. Sub-lethal effects of CPZ on planarians included reductions in locomotion (1.8 mg/L), delayed photoreceptors regeneration (from 0.45 mg/L), and feeding inhibition (5.6 mg/L). Our results confirm the moderate toxicity of CPZ towards aquatic invertebrates but sub-lethal effects observed also suggest potential chronic effects of CPZ with consequences for population dynamics.
Keywords: Aquatic Organisms; Triazoles; sladká voda; Water Pollutants, Chemical; zvířata; ploštěnky; vodní organismy; Lethal Dose 50; Ecotoxicology; Planarians; Dose-Response Relationship, Drug; Animals; vztah mezi dávkou a účinkem léčiva; LD50; ekotoxikologie; chemické látky znečišťující vodu; triazoly; Chironomidae; Fresh Water